Srtsabc Based Self-Regulating Routing Algorithm (Sr3ta(R)) - et. al., D.Gopinath, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
MANETs (Mobile Ad Hoc Networks) are unique types of decentralised wireless networks that do not need any pre-existing communication infrastructure between the nodes. In Mobile Ad Hoc Networks, each node is involved in routing by forwarding data packets to other nodes, and thereby determining the nodes are dynamically forwarded on the basis of network connectivity. The establishment of an efficient routing mechanism for communication between nodes as these nodes move freely with constantly changing topology is one of the important issues in MANETs. In order to keep track of the constantly changing topology of the network, successful optimised techniques are needed. In this paper, hereby propose a SRTSABC Based Self-Regulating Routing Algorithm SR3TA(R) by considering a random set of source and destination nodes and exchanges between them by the Bees. The pheromone tables and data structures are produced during the movement of bees to record the trip time of the nodes. Extensive simulations are conducted to assess the efficacy of the proposed algorithm by manipulating various parameters. The final results obtained are compared with two well known algorithms namely as ZBMRP, DCFP and FF-AOMDV. SR3TA(R) Algorithm with regard to different performance metrics such as the number of data packets sent, Throughput, End-to - End delay and Latency. The final results obtained show that the performance of the proposed SR3TA(R) algorithm is greater than the ZBMRP, DCFP and FF-AOMDV algorithms.